Hubungan Pemberian Makanan Tambahan Terhadap Perubahan Status Gizi Anak Balita Gizi Kurang di Kota Manado - Hosang, Kevin H.; Umboh, Adrian; Lestari, Hesti (e-CliniC, 2017)
Abstract: Toddler is one of the nutritional vulnerable population groups that easily suffer from health problems and malnutrition. In this age group, children are in growth and development cycle that requires nutrients in larger amounts than any other age groups. To overcome the problem of malnutrition in this age group, they should be supported with supplementary food. Pemberian makanan tambahan (PMT) is a program of intervention to infants suffering from malnutrition with a goal to improve the nutritional status as well as the nutritional needs of children to achieve the nutritional status and condition of good nutrition in accordance with the children's age. PMT for children aged 0-59 months is as an addition and not as a substitute of main daily meals. This study was aimed to determine the relationship of supplementary feeding to changes in the nutritional status of children under 5 years with malnutrition at health centers in Manado. This was an analytical retrospective study. Subjects were 70 children under 5 years with malnutrition fed with rice, biscuits, green beans, and milk for 90 days. The results showed that there was a very significant relationship between PMT and the changes in nutritional status of children under 5 years with malnutrition at health centers in Manado.Keywords: feeding (PMT), toddler, child nutritional statusÂ Abstrak: Balita merupakan salah satu golongan penduduk rentan gizi yang paling mudah menderita gangguan kesehatan dan kekurangan gizi. Kelompok usia tersebut berada pada suatu siklus pertumbuhan atau perkembangan yang memerlukan zat-zat gizi dalam jumlah yang lebih besar dari kelompok umur yang lain. Untuk mengatasi masalah gizi pada kelompok usia tersebut perlu diselenggarakan pemberian makanan tambahan (PMT). PMT merupakan program intervensi terhadap balita yang menderita kurang gizi yang bertujuan untuk meningkatkan status gizi anak dan mencukupi kebutuhan zat gizi anak sehingga tercapainya status gizi dan kondisi gizi yang baik sesuai dengan usia anak tersebut. PMT bagi anak usia 0-59 bulan sebagai tambahan, bukan sebagai pengganti makanan utama sehari-hari. Penelitian ini bertujuan untuk mengetahui hubungan pemberian makanan tambahan terhadap perubahan status gizi anak balita gizi kurang di Puskesmas-puskesmas di Kota Manado. Jenis penelitian ialah analitik retrospektif. Subjek penelitian ialah 70 anak balita gizi kurang yang mendapatkan PMT berupa beras, biskuit, kacang hijau, dan susu selama 90 hari. Hasil penelitian menunjukkan bahwa PMT berpengaruh sangat bermakna terhadap perubahan status gizi anak balita gizi kurang di puskesmas-puskesmas Kota Manado.Kata kunci: PM), balita, status gizi, balita gizi kurang